The Effect of Proposed Offense Game Building (Creative Space and occupying it area 14 for wings in (7 Seconds) For Developing Some Planning Skills in Youth Soccer Players - Shlaqa, Ali Jasem; Altemimi, Abdalhadi Hameed (Journal of Physical Education, 2022)
The research problem lies in not being able to deliver the ball quickly enough nor high enough resulting in weakness in planning. The research aimed at identifying offensive strategy effect (creating a space then occupying it in area14 for wing players in 7 seconds for developing planning skills. The subjects were (26) youth soccer players; (6) were selected for pilot study and 20 were divided into two equal groups. The researcher concluded that using this strategy develop planning skills in youth soccer players.